Students Incubator Business: A Mentorship Program for Creating Promotional Media for Student Micro Businesses Using Canva - Karina, Anggita Ajeng; Erinda, Hayyu; Wijaya, Dandi Nurmansyah; Nikma, Irfianinza Risqulia; Yuliono, Gun; Ulum, Miftahul; Widayanti, Erma; Christianto, Yudhi (Universitas Negeri Malang, 2024)
The